A multicenter, phase 3, randomized trial of concurrent chemoradiotherapy plus adjuvant chemotherapy versus radiotherapy alone in patients with regionally advanced nasopharyngeal carcinoma: 10‐year outcomes for efficacy and toxicity. Issue 21 (29th June 2017) - Lee, Anne W. M.; Tung, Stewart Y.; Ng, Wai Tong; Lee, Victor; Ngan, Roger K. C.; Choi, Horace C. W.; Chan, Lucy L. K.; Siu, Lillian L.; Ng, Alice W. Y.; Leung, To Wai; Yiu, Harry H. Y.; O'Sullivan, Brian; et al.
Abstract : BACKGROUND: Concurrent‐adjuvant chemoradiotherapy (CRT) became a recommended treatment for locoregionally advanced nasopharyngeal carcinoma (NPC) with the first report of a significant survival benefit from the Intergroup 0099 study. However, data on late toxicities are lacking. Previous reports from the current NPC‐9901 trial have raised concerns about a failure to improve overall survival (OS) because of an inadequate impact on distant control and increases in toxicities/noncancer deaths. Validation of the long‐term therapeutic ratio is needed. METHODS: In this phase 3, randomized trial, patients with nonkeratinizing NPC (stage T1‐4/N2‐3/M0) were randomly assigned to radiotherapy alone (176 patients) or to CRT (172 patients) with concurrent cisplatin followed by adjuvant cisplatin plus fluorouracil. RESULTS: The early findings of significant improvements in tumor control were maintained: the CRT group achieved significantly higher 10‐year overall failure‐free (62% vs 50%; P = .01) and progression‐free survival rates (56% vs 42%; P = .006) because of superior locoregional control (87% vs 74%; P = .003), whereas the impact on distant control remained insignificant (68% vs 65%; P = .24). The initial differences in toxicities diminished with longer follow‐up: 52% versus 47% at 10 years for late toxicities ( P = .20), 4.1% versus 2.8% for deaths due to treatment toxicity, and 15.1% versus 13.1% for deaths due to incidental/unknown causes. The OS rate for the CRT group reached statistical superiority at 10 years (62% vs 49%; P = .047). CONCLUSIONS: Long‐term results have confirmed that CRT can significantly improve OS without excessive late toxicities for patients with regionally advanced NPC. However, more potent therapy is needed for improving distant control, especially for patients with stage IVA/B disease. Cancer 2017;123:4147–4157. © 2017 American Cancer Society . Abstract : Compared with radiotherapy alone, concurrent chemotherapy and adjuvant chemotherapy could significantly improve overall survival for patients with regionally advanced nasopharyngeal carcinoma without an excessive increase in late toxicities.